Pelatihan Pembuatan Lubang Resapan Biopori Untuk Penanganan Genangan Air di Desa Molingkapoto - Risti Ristianingsih Badu; Wahidin Lukum; M. Rachmat Tahir (Madani: Jurnal Pengabdian Ilmiah, 2023)
Molingkapoto Village is one of the villages in North Gorontalo Regency most often affected during the rainy season. The way to overcome this problem is to use flood management technology, namely Biopore Infiltration Holes (LBR). This activity aims to teach people about other ways to prevent flooding and reduce waterlogging during the rainy season. The training participants were the people of Molingkapoto Village. The method used is a field survey, a participatory approach by providing socialization and technical training on how to make Biopore Infiltration Holes (LBR). The results of socialization and training show that the enthusiasm of the people of Molingkapoto Village in reducing the impact of high rainfall every day is very large. Making Biopori Infiltration Holes (LBR) was carried out at 12 points of residents' houses and village public facilities. The choice of location for the installation of the Biopori Infiltration Hole (LBR) was based on the results of a survey of locations that are often affected during the rainy season. This service activity provides positive benefits for the people of North Gorontalo Regency, especially in overcoming the problem of flooding and standing water sustainably.